Nitrogen form and concentration interact to affect the performance of two ecologically distinct Mediterranean forest trees - Uscola, Mercedes; Oliet, JuanA.; Villar-Salvador, Pedro; Díaz-Pinés, Eugenio; Jacobs, DouglassF. (European Journal of Forest Research, 2014)
Most studies examining inorganic N form effects on growth and nutrition of forest trees have been conducted on single species from boreal or temperate environments, while comparative studies with species from other biomes are scarce. We evaluated the response of two Mediterranean trees of contrasting ecology, Quercus ilex L. and Pinus halepensis Mill., to cultivation with distinct inorganic N forms. Seedlings were fertilized with different NH4 (+)/NO3 (-) proportion at either 1 or 10 mM N. In both species, N forms had small effects at low N concentration, but at high N concentration they markedly affected the plant performance. A greater proportion of NH4 (+) in the fertilizer at high N caused toxicity as it reduced growth and caused seedling death, with the effect being greater in Q. ilex than in P. halepensis. An increase in the proportion of NO3 (-) at high N strongly enhanced growth relative to low N plants in P. halepensis but had minor effects in Q. ilex. Relatively more NH4 (+) in the fertilizer enhanced plant P concentration but reduced K concentration in both species, while the opposite effect occurred with NO3 (-), and these effects were enhanced under high N concentration. We conclude that species responses to inorganic N forms were related to their ecology. P. halepensis, a pioneer tree, had improved performance with NO3 (-) at high N concentration and showed strong plasticity to changes in N supply. Q. ilex, a late successional tree, had low responsiveness to N form or concentration.
Keywords: ammonium; ecophysiology; Growth; nitrate; Pinus halepensis; Quercus ilex

Spatial distribution of the soil organic carbon pool in a Holm oak dehesa in Spain - Simón, Nuria; Montes, Fernando; Díaz-Pinés, Eugenio; Benavides, Raquel; Roig, Sonia; Rubio, Agustín (Plant and Soil, 2012)
Aims Dehesas are agroforestry systems characterized by scattered trees among pastures, crops and/or fallows. A study at a Spanish dehesa has been carried out to estimate the spatial distribution of the soil organic carbon stock and to assess the influence of the tree cover. Methods The soil organic carbon stock was estimated from the five uppermost cm of the mineral soil with high spatial resolution at two plots with different grazing intensities. The Universal Kriging technique was used to assess the spatial distribution of the soil organic carbon stocks, using tree coverage within a buffering area as an auxiliary variable. Results A significant positive correlation between tree presence and soil organic carbon stocks up to distances of around 8 m from the trees was found. The tree crown cover within a buffer up to a distance similar to the crown radius around the point absorbed 30 % of the variance in the model for both grazing intensities, but residual variance showed stronger spatial autocorrelation under regular grazing conditions. Conclusions Tree cover increases soil organic carbon stocks, and can be satisfactorily estimated by means of crown parameters. However, other factors are involved in the spatial pattern of the soil organic carbon distribution. Livestock plays an interactive role together
Keywords: agroforestry systems; Soil C; Spatial variance partition; Tree effect; Universal Kriging